2021
DOI: 10.1007/s13280-021-01539-5
|View full text |Cite
|
Sign up to set email alerts
|

Setting population-size targets for geese causing socio-economic conflicts

Abstract: Most European goose populations have increased exponentially, and this has increasingly brought them into conflict with human activities. To manage this conflict, we used multi-criteria decision analysis to help set population targets for a super-abundant population of greylag geese (Anser anser). We relied on expert elicitation to assess the consequences of varying goose abundance on nine ecological, economic, and societal objectives. Representatives from national governments and from non-governmental organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For the calculation of the daily MCPs, data were merged from the years 2014 to 2021. periods for population size assessment. Comparing satellite tracking and data indicated that current autumn and spring count schemes likely underestimate true population size, even though spring and autumn counts generally exceed the corresponding winter counts (Johnson et al, 2021). Our findings provide important perspectives to be considered when studying migratory connectivity and assessing the population size of the taiga bean goose population and migratory animal populations in general.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…For the calculation of the daily MCPs, data were merged from the years 2014 to 2021. periods for population size assessment. Comparing satellite tracking and data indicated that current autumn and spring count schemes likely underestimate true population size, even though spring and autumn counts generally exceed the corresponding winter counts (Johnson et al, 2021). Our findings provide important perspectives to be considered when studying migratory connectivity and assessing the population size of the taiga bean goose population and migratory animal populations in general.…”
Section: Discussionmentioning
confidence: 79%
“…These are probably caused by birds moving further south (especially to Germany) during cold winters and the lack of any available count data from Germany (Heldbjerg et al, 2019). As results from the Swedish mid-winter counts are used in the integrated population model (Johnson et al, 2021) to monitor the taiga bean goose population size for the purposes of international management, it would be important to study their performance in the future. In addition, it would be vital to develop mid-winter counts also in Germany and to merge these data with the Swedish count data.…”
Section: Nonbreeding Distribution and Estimation Of Taiga Bean Goose ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we used estimates of population size of 40.96 thousand (SD = 3.33) and a harvest of 7.26 thousand (SD = 0.131) from 2000 based on an update of an integrated population model (IPM) by Johnson et al. (2020). We also examined estimates from 2020 after population size had increased to 62.16 thousand (SD = 2.02) and harvest had been reduced to 3.56 thousand (SD = 0.14).…”
Section: Worked Examples Of Popharvestmentioning
confidence: 99%